Two Volumes on the Great Patriotic War – General Rehearsal of a Twelve Volume Work (Zolotarev V.A., Sokolov A.M. The History of the Great War. 1941 – 1945: 2 v. М., 2010) - A. A. Paderin (Vestnik MGIMO-Universiteta)
.